2021
DOI: 10.3389/fonc.2021.652133
|View full text |Cite
|
Sign up to set email alerts
|

A Key Pathway to Cancer Resilience: The Role of Autophagy in Glioblastomas

Abstract: There are no effective strategies for the successful treatment of glioblastomas (GBM). Current therapeutic modalities effectively target bulk tumor cells but leave behind marginal GBM cells that escape from the surgical margins and radiotherapy field, exhibiting high migratory phenotype and resistance to all available anti-glioma therapies. Drug resistance is mostly driven by tumor cell plasticity: a concept associated with reactivating transcriptional programs in response to adverse and dynamic conditions fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 227 publications
(263 reference statements)
0
9
0
Order By: Relevance
“…Autophagy plays a central role in cancer progression [ 93 ]. In glioma, autophagy is believed to be an adaptive MoA used by glioma cells to protect them from unfavorable conditions [ 94 ].…”
Section: The Case Of Galectin-8mentioning
confidence: 99%
“…Autophagy plays a central role in cancer progression [ 93 ]. In glioma, autophagy is believed to be an adaptive MoA used by glioma cells to protect them from unfavorable conditions [ 94 ].…”
Section: The Case Of Galectin-8mentioning
confidence: 99%
“…Despite the progress in cancer treatments, almost no advancement in the therapy of gliomas has been introduced; those brain tumors display stemness signatures, and new strategies against the highly proliferative activity of glioma cells have been studied and new compounds acting against them are needed. , These new agents need to penetrate the blood–brain barrier, then also penetrate through the tissue of the whole brain, and selectively eliminate cancer cells without harming the normal brain tissue. , The malignant glioma resistance to chemotherapy , suggests that cancer therapy should include agents that target residual cells to prevent the regrowth of neoplastic cells . Numerous molecular and cellular targets are described as a possibility in GBM treatment, , and modulation of the autophagic flux is one of them. …”
Section: Introductionmentioning
confidence: 99%
“…A recent review concluded that most of the studies indicating autophagic cell death in response to treatment were in vitro studies using high doses, whereas clinical and pre-clinical studies indicated that autophagy was a protective mechanism. 132 Therefore, they hypothesised that autophagy is a protective mechanism in GBM therapy response, but very high levels of stress can over-activate autophagy, leading to cell death. 132 Similarly, the authors of a review paper suggested that the level of ER stress may determine the role of autophagy.…”
Section: 12: Glioblastoma (Gbm)mentioning
confidence: 99%
“…132 Therefore, they hypothesised that autophagy is a protective mechanism in GBM therapy response, but very high levels of stress can over-activate autophagy, leading to cell death. 132 Similarly, the authors of a review paper suggested that the level of ER stress may determine the role of autophagy. 133 They suggested that up to moderate levels of stress, the ER unfolded protein response (UPR) pathway led to initiation of autophagy to remove damaged cellular components and thereby protect cells from apoptosis.…”
Section: 12: Glioblastoma (Gbm)mentioning
confidence: 99%
See 1 more Smart Citation